Cardiovascular risk in patients with chronic obstructive pulmonary disease and metabolic syndrome - S. Nikolaeva; A. Angelov (Българска кардиология, 2023)
Chronic obstructive pulmonary disease is a cause of morbidity and mortality worldwide. The presence of infl ammatory markers in circulation, sputum, and broncho-alveolar fl uid suggest systemic infl ammation is one of the potential mechanisms responsible for both chronic obstructive pulmonary disease and metabolic syndrome. Circulating markers of infl ammation, on the other hand, are those that have been found to predict future cardiovascular events as well. One of the main causes of increased cardiovascular risk in patients with chronic obstructive pulmonary disease and metabolic syndrome is hyperglycemia. It induces oxidative stress and subsequently micro- and macrovascular complications. This review describes in details the various components of metabolic syndrome and its impact on long outcomes in chronic obstructive pulmonary disease and cardiovascular pathology.